CD44v6: A metastasis-associated biomarker in patients with gastric cancer?: A comprehensive meta-analysis with heterogeneity analysis - Lu, Li (Medicine (Baltimore), 2016)
BACKGROUND: The diagnostic and prognostic value of CD44v6 in patients with gastric cancer remains unclear. Therefore, a quantitative meta-analysis was conducted to determine the clinical value of CD44v6 in patients with gastric cancer. METHODS: Sixteen studies with 2177 patients were included. Pooled odds ratios (ORs) and hazard ratio (HR) with 95% confidence intervals (CIs) were calculated to estimate the impact of CD44v6 in patients with gastric cancer on clinicopathological features and 5-year overall survival (OS). Sensitivity analysis, subgroup analysis, and regression analysis were introduced to evaluate the heterogeneity across the studies. Publication bias was also explored among the studies. RESULTS: The meta-analysis showed that the upregulated CD44v6 was associated with lymph node metastasis (OR 1.91, 95% CI 1.19–3.08; P = 0.007), distant metastasis (OR 3.41, 95% CI 2.01–5.78; P = 0.000), high TNM stage (OR 2.29, 95% CI 1.10–4.75; P = 0.026), lymphatic vessel invasion (OR 1.59, 95% CI 1.21–2.09; P = 0.001), and vascular invasion (OR 1.57, 95% CI 1.19–2.07; P = 0.001). When excluded 1 study based on sensitivity analysis, pooled HR indicated that CD44v6 positive expression was correlated poor 5-year OS (OR 1.76, 95% CI 1.30–2.39; P = 0.000), meanwhile, heterogeneity was eliminated. The heterogeneity of Lauren type mainly existed in the big sample size subgroup. Different region and publication year might contribute to the heterogeneity of differentiation type. While the heterogeneity of lymph node mainly existed in Asian and big sample size group. Publication bias was observed among 12 studies on lymph node metastasis (P(publication bias) = 0.041), and 5 studies on TNM stage (P(publication bias) = 0.026). CONCLUSION: Taken together, CD44v6 overexpression might be correlated to the characteristics of tumor metastasis in gastric cancer, consisting with many mechanism studies. Therefore, CD44v6 might present a metastasis-associated biomarker in patients with gastric cancer.